First Record of Venturia sp. Parasitizing the Coconut Moth - Queiroz, Abel Felipe Oliveira; Ambrogi, Bianca Giuliano; Santos, Jucileide Lima; Nascimento, Eduardo Silva (EntomoBrasilis, 2015)
The coconut moth Atheloca subrufella Hulst (Lepidoptera: Pyralidae) is considered an important pest of coconut crops in Brazil, which is the fourth largest global coconut producer. Concerning the economic importance of this crop and aiming to increase the knowledge related to biological control, the present research aimed records the first occurrence of Venturia sp. (Hymenoptera: Ichneumonidae) parasitizing A. subrufella caterpillars in the State of Sergipe, Brazil. Coconuts infested by A. subrufella caterpillars were collected in coconut plantation and kept in the Entomology Laboratory (Universidade Federal de Sergipe – UFS) until the emergence of A. subrufella adults or the parasitoids. The parasitoids obtained were identified as Venturia sp.. Primeira ocorrência de Venturia sp. Parasitando a Traça-do-Coqueiro Resumo. A traça-do-coqueiro Atheloca subrufella Hulst (Lepidoptera: Pyralidae) é considerada uma importante praga da cultura do coqueiro no Brasil, o qual é o quarto maior produtor mundial de coco. Devido à importância econômica desta cultura e visando aumentar o conhecimento relacionado ao controle biológico, o presente trabalho teve como objetivo relatar a primeira ocorrência de Venturia sp. (Hymenoptera: Ichneumonidae) parasitando lagartas de A. Subrufella no estado de Sergipe, Brasil. Cocos infestados por lagartas de A. subrufella foram coletados em plantações de coco e mantidos no laboratório de Entomologia (Universidade Federal de Sergipe – UFS) até a emergência de adultos de A. subrufella ou dos parasitoides. Os parasitoides obtidos foram identificados como Venturia sp..